Ground movement prediction due to block caving mining geometry using GIS - Agung Setianto; Eman Widijanto (Geological Engineering Department Universitas Gadjah Mada, 2015)
Large scale block cave mining has been operated for over 30 years in the Erstberg Mining District in the province of Papua, Indonesia. The ore body is divided into four vertically stacked ore bodies: Gunung Bijih Timur (GBT), Intermediate Ore Zone (IOZ), Deep Ore Zone (DOZ), and Deep Mill Level Zone (DMLZ). The GBT and IOZ mines were closed on 1993 and 2003, DOZ mine is in its peak production performance 80 ktpd, and DMLZ mine is still in the development stage to prepare mine infrastructures. This situation generates gradual downward settling of the surface or subsidence. Significant deformation changes at the surface by block caving subsidence could damage the mine’s infrastructures in surface and underground and also affect geological structures overlying the mining areas which may result in surface impacts on the natural geomorphology and land use. In this paper, integrated system based on Geographic Information System (GIS) platform applied to predict ground movements due to underground mining. Deep Ore Zone (DOZ) block cave mine is studied for subsidence prediction. The mining extraction thickness model is obtained from height of draw (HOD) observed data. Subsidence Engineering Handbook (SEH) of empirical model and measured data from mining fields is used for subsidence calculation parameters. The calculations were performed in GIS. The maximum vertical displacement has been predicted about 12m by means of full caving mining method. Keywords: Ground movements, block caving, GIS, underground mining, and subsidence